Patagomaia could be a gondwanatherian - Püschel, Hans P. (2024)
In a recent contribution, Chimento et al. described fragments of the pelvis and hindlimb of a Late Cretaceous mammal from the Campanian–Maastrichtian Chorrillo Formation (Southern Patagonia, Argentina). They named a new genus and species, Patagomaia chainko, and assigned it to Theria, representing, in their opinion, the definitive first record of this clade in the Late Cretaceous of South America (other alleged therians were discussedby Rougier et al. who considered their assignment ambiguous). Here, we argue that an important alternative was not properly assessed: Patagomaia may be a gondwanatherian, a clade whose presence in South America is well-documented. Chimento et al. carried out a single phylogenetic analysis that included a gondwanatherian: Adalatherium hui, from the Late Cretaceous of Madagascar, which is the only gondwanatherian for which associated, almost complete postcranial remains are known. Upon comparing Patagomaia and Adalatherium, we have found that all putatively therian characters of Patagomaia mentioned by Chimento et al. are either present in Adalatherium, or cannot be assessed in the latter. Further, several characters were incorrectly scored in the phylogenetic analyses of Chimento et al.. When these scores are corrected, there is no longer support for therian affinities; instead, gondwanatherian affinities are found to be more plausible.